Hubungan Kualitas Tidur dengan Konsentrasi pada Mahasiswa preklinik Fakultas Kedokteran Universitas Palangka Raya Tahun 2022 - Muhtazah, Farida; Kahanjak, Donna; Nugrahini, Sintha (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Concentration is centralization of the mind, motivation towards something with the addition of feeling worried, depressed, and panic so as not to hinder one's readiness. One of the factors that make it difficult to concentrate is the quality of sleep. Students can experience concentration problems, especially medical students because of the limited quality and quantity of sleep. Therefore, researchers are interested in conducting research on the relationship between sleep quality and concentration in preclinical students at the Faculty of Medicine, University of Palangka Raya. This study used an analytic observation method with a cross-sectional design. The research sample was 212 preclinical students in 2019, 2020 and 2021 who met the inclusion and exclusion criteria. Sampling technique with proportionate stratified random sampling. The instruments in this study were the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality and the Stroop Test to assess concentration. This study showed that out of 212 samples, 55 people had good sleep quality and 157 had poor sleep quality. Only 39 people with good sleep quality had good concentration. There are 120 students with poor sleep quality but have good concentration. The results of the analysis showed with the Chi Square P Value test (0.416 > 0.05) that there was no significant relationship or relationship between sleep quality and concentration in preclinical students at the Faculty of Medicine, University of Palangka Raya.